QiShenYiQi Inhibits Tissue Plasminogen Activator–Induced Brain Edema and Hemorrhage after Ischemic Stroke in Mice - Ye, Yang; Li, Quan; Pan, Chun-Shui; Yan, Li; Sun, Kai; Wang, Xiao-Yi; Yao, Shu-Qi; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Pharmacology, 2022)
Background: Thrombolysis with tissue plasminogen activator (tPA) remains the only approved drug therapy for acute ischemic stroke. However, delayed tPA treatment is associated with an increased risk of brain hemorrhage. In this study, we assessed whether QiShenYiQi (QSYQ), a compound Chinese medicine, can attenuate tPA-induced brain edema and hemorrhage in an experimental stroke model. Methods: Male mice were subjected to ferric chloride-induced carotid artery thrombosis followed by mechanical detachment of thrombi. Then mice were treated with QSYQ at 2.5 hours followed by administration of tPA (10 mg/kg) at 4.5 hours. Hemorrhage, infarct size, neurological score, cerebral blood ﬂow, Evans blue extravasation, FITC-labeled albumin leakage, tight and adherens junction proteins expression, basement membrane proteins expression, matrix metalloproteinases (MMPs) expression, leukocyte adhesion, and leukocyte infiltration were assessed 24 hours after tPA administration. Results: Compared with tPA alone treatments, the combination therapy of QSYQ and tPA significantly reduced hemorrhage, infarction, brain edema, Evans blue extravasation, albumin leakage, leukocyte adhesion, MMP-9 expression, and leukocyte infiltration at 28.5 hours after stroke. The combination also significantly improved the survival rate, cerebral blood ﬂow, tight and adherens junction proteins (occludin, claudin-5, junctional adhesion molecule-1, zonula occludens-1, VE-cadherin, α-catenin, β-catenin) expression, and basement membrane proteins (collagen IV, laminin) expression. Addition of QSYQ protected the downregulated ATP 5D and upregulated p-Src and Caveolin-1 after tPA treatment. Conclusion: Our results show that QSYQ inhibits tPA-induced brain edema and hemorrhage by protecting the blood-brain barrier integrity, which was partly attributable to restoration of energy metabolism, protection of inflammation and Src/Caveolin signaling activation. The present study supports QSYQ as an effective adjunctive therapy to increase the safety of delayed tPA thrombolysis for ischemic stroke.